Short stature: an ordinary sign for an unordinary diagnosis - Paolo Cavarzere; Valentina Bortolotti; Michela Capogna; Margherita Guarnieri; Francesca Lucca; Rossella Gaudino; Stefano Marzini; Claudia Banzato; Franco Antoniazzi (BMC, 2017)
Abstract Background Short stature (SS) is a relatively early sign of poor health. Only in 5% of cases we can explain it through the presence of endocrinological pathologies. Therefore, if SS is present since the first months of life, it is necessary to investigate all systemic disorders with secondary effects on growth. Case presentation We report the case of a 16-months-old male infant with severe SS apparently not associated with other clinical signs or symptoms. The patient arrived to our attention after he was hospitalized for an Echovirus enteritis, associated to moderate neutropenia (800/mm3) and hypertransaminasemia (AST 116 U/L, ALT 88 U/L) at the age of 13 months. SS was detected in that occasion. Since SS persisted even after the complete resolution of enteritis symptoms, he was taken care by our unit. Conclusions SS appeared in the first months of life and associated with moderate neutropenia and hypertransaminasemia led us to the diagnosis of Shwachmann-Diamond syndrome. We recommend paying further attention to this condition during the differential diagnosis of children with severe SS.